Bohemian editors and translators at the turn of the 16th century - Vaculínová, Marta; Storchová, Lucie; Slavíková, Marcela; Neškudla, Bořek; Podavka, Ondřej; Králová, Magda (2021)
The volume with a joint introductory chapter is in the first part devoted to Humanists publishing in the circle of the university of Leipzig at the turn of the 15th century: Paulus Niavis / Schneevogel (ca. 1453–1517) and Ioannes Honorius Cubitensis (ca. 1465–1504). The second part includes the translation work of Řehoř Hrubý of Jelení (ca. 1460–1514), mostly preserved in manuscript, the first translation from Ancient Greek into Czech by Václav Písecký (ca. 1482–1511), and a remarkable edition of Martianus Capella’s work De nuptiis Philologiae et Mercurii prepared by Ioannes Dubravius (ca. 1486–1553). The volume covers a relatively short period beginning in 1488, when the editions of Niavis and Honorius are first documented in Leipzig, and ending with 1516, when Dubravius’s edition of Martianus Capella was published in Vienna.